Lesões músculo-esqueléticas relacionadas com as atividades desportivas em crianças e adolescentes: Uma revisão das questões emergentes | [Sports related musculoskeletal disorders in children and adolescents: A review of the emerging issues] - Maria Eugénia Pinho (2013)
Regular physical activity promotes better general state of health and is essential for the prevention of many illnesses, including musculoskeletal disorders. The promotion of both physical activity and its beneficial effects on health have contributed to the fast growth in the number of children and adolescents involved in organized or recreational sports activities which, unfortunately, has been followed by a significant increase on the number of injuries related to its practice. Taking into account that children and adolescents musculoskeletal system is still developing, its overuse particularly associated to competition sports activities may have long-term effects on their health. This paper aims to review the main questions of sports-related musculoskeletal disorders in children and adolescents, including the involved ethical issues, as well as to identify some of the main risk factors and to point out some of the measures to be adopted for its prevention.